2022
DOI: 10.3390/land11050633
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Formalization of Rural Land Transactions in Ethiopia: A Theory of Planned Behavior Approach

Abstract: Despite the recent successful establishment of systematic land registration programs in some African countries including Ethiopia, updating the land registers has become a growing concern. However, there is limited empirical evidence about whether landholders’ behavior is driving the lack of updating land registers in Ethiopia. Using the theory of planned behavior, this study examines the factors that influence landholders’ behavior of formalizing rural land transactions in Ethiopia. Primary and secondary data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The model utilized in this study encompassed 5 latent variables and 17 observable indicators associated with these variables. Following the approach employed by Abab et al (2022), the minimum required sample size of 150 was calculated using the Soper online free statistical calculator. The estimated parameters and values are presented in Table 4.…”
Section: Data Collectionmentioning
confidence: 99%
“…The model utilized in this study encompassed 5 latent variables and 17 observable indicators associated with these variables. Following the approach employed by Abab et al (2022), the minimum required sample size of 150 was calculated using the Soper online free statistical calculator. The estimated parameters and values are presented in Table 4.…”
Section: Data Collectionmentioning
confidence: 99%
“…In a formal system or statutory context, land titling is sought as one of the mechanisms that provide rights holders with a secure tenure right and incentivizes them to use land efficiently by investing in land conservation and improvement [5,18]. Since early 2000, the government of Ethiopia has launched one of the biggest two-stage land registration and certification programs in Africa with the aim to improve land tenure security in the highlands of Ethiopia and incentivize long-term land-based investment such as SLM practices and curb land degradation [31].…”
Section: Whether De Facto Land Tenure Security Influences Landholders...mentioning
confidence: 99%
“…Notwithstanding this, since 2020, access to information by the rightsholders about their legal rights from woreda digital land registers has improved when the need arises to process credit applications. Abab et al [23] found that all mortgages or credit transactions had been registered in the digital land registers in Basona worena woreda of Ethiopia, where the system has been up and running since 2019. Results from the digital land registers of the current study show that the total number of households who received SLLC-linked credits was 10,789 with a credit value of 8 million US dollars equivalent, although only 3% of smallholder households obtained this volume of credit in the study kebeles.…”
Section: Whether Access To Digital Land Registers Signals Credit-wort...mentioning
confidence: 99%
“…Historically, the FLLC started around the end of the 1990s and ran through 2010. In contrast, the SLLC pilots have been started since 2003 and run through 2013 [23]. Since 2014, the SLLC rollout program has been launched nationwide and continued expanding in the highland parts of the country to date [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation